2015
DOI: 10.1080/1068316x.2015.1077248
|View full text |Cite
|
Sign up to set email alerts
|

Can someone fabricate verifiable details when planning in advance? It all depends on the crime scenario

Abstract: In the current study we examined the effect of having the opportunity to plan an alibi in advance on the suitability of the verifiability approach in two crime scenarios that differed in their opportunity to carry out innocent activities at the time of the crime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…Thus, an investigator should consider whether the presence of the suspect at the crime scene when the crime took place is legitimate. If this is the case, the investigator should be aware that a suspect could tell an embedded lie (see Nahari & Vrij, 2015), and thus should be careful with interpreting their richness in detail scores.…”
Section: Type Of Liementioning
confidence: 99%
“…Thus, an investigator should consider whether the presence of the suspect at the crime scene when the crime took place is legitimate. If this is the case, the investigator should be aware that a suspect could tell an embedded lie (see Nahari & Vrij, 2015), and thus should be careful with interpreting their richness in detail scores.…”
Section: Type Of Liementioning
confidence: 99%
“…In the first application of the VA to the insurance claims domain, it was found that verifiable details did not discriminate between liars and truth tellers (Nahari et al ., ). The authors reasoned that liars used embedding strategies, which allowed them to report sufficient checkable detail to appear credible due to the context in which the lie is told (Nahari & Vrij, ). Recently, Vrij, Nahari, and Isitt () replicated Nahari et al .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it was not logical for truth-tellers to receive instructions about a forthcoming interview. Previous deception studies have used similar designs that excluded truth-tellers where the scenario would not apply to innocent suspects (Honts et al, 1994;Nahari & Vrij, 2015;Tekin, Granhag, Strömwall, & Vrij, 2016).…”
Section: The Current Studymentioning
confidence: 99%
“…Accordingly, it was not logical for truth-tellers to receive instructions about a forthcoming interview. Previous deception studies have used similar designs that excluded truth-tellers where the scenario would not apply to innocent suspects (Honts et al, 1994;Nahari & Vrij, 2015;Tekin, Granhag, Strömwall, & Vrij, 2016).One way liars can cover up for their crime is by providing a false alibi. As it is common for liars to provide information about events they have experienced (Culhane, Hosch, & Kehn, 2008;Leins, Fisher, & Ross, 2013), they would want to familiarise themselves with the alibi setting to be able to demonstrate they were at the setting when the the current study examines cases in which suspects provide an alibi for a location they visited only on the date the crime occurred.…”
mentioning
confidence: 99%